Design and Optimization of Novel Sugar Alcohol Based Extended Release Tablets Prepared by Melt Dispersion Technique: Sugar alcohol as controlled release carrier - Balamurugan Jeganathan,; Vijayalakshmi Prakya, (Iranian Journal of Pharmaceutical Sciences, 2012)
The aim of this study is to prepare novel sorbitol based extended release tablets by melt dispersion method using carbamazepine as a model drug. Carbamazepine was melted along with sugar alcohol to get melt dispersion granules (MGDs) and was characterized by differential scanning calorimetry (DSC), powder X-ray diffractometry (XRD) and solubility study. The physical and chemical parameters of MDGs and tablets were measured while drug release was studied using USP II dissolution apparatus. The release data were subjected to different models to evaluate their release kinetics and mechanisms. Evaluation of MDGs using XRD and DSC indicated that melt dispersion process converted crystalline carbamazepine and sugar alcohol into lower crystallinity with no significant improvement in solubility. The drug release rate was found to be affected by sugar alcohol concentration, particle size of MDGs, the nature of co-excipients, agitation rate and hardness. The kinetics of carbamazepine release from formulation (F3) showed best fit to Higuchi and super case II transport mechanism. It can be concluded that sorbitol is a suitable matrix-forming agent to sustain the release of low soluble drug carbamazepine. Melt dispersion technique using sorbitol is proved to be a promising technique for controlled drug delivery.